An Analysis of the Transformation of Social Media to “Social Factory” -Based on the Perspective of Communication Political (Asian Journal of Social Science Studies, 2022)
With the advent of the Web2.0 era, human nature‟s desire for communication has been activated at the technical level. While more and more users are using social media, Internet-related companies are also trying their best to satisfy people‟s fantasies about the form of communication by developing various new forms of social software. However, in fact, many social media are under the guises of social media, but their essence is the logic of capital. From the perspective of the political economy of communication, this paper argues that social media has become a “social factory”, and with the expansion of the “social factory”, the entire society will gradually become factory-like.